Fluorometric combination analysis of conformational changes in urea-induced unfolding of soybean protein isolates and their complexes with casein - Yangchao Gao; Yuchuan Li; Yifan Yang; Hongying He; Yanqiong Li; Shuhui Yu; Haiying Wang; Yuyu Zhang; He Liu (PLoS ONE, 2025)
Soybean proteins isolates (SPIs) could misfold to form amorphous aggregates after unfolding due to processing conditions, leading to a decrease in their solubility, and casein might be able to block the formation of amorphous aggregates. The turbidity curves showed that SPIs/7S/11S could maintain a soluble state in the presence of casein. The folding and unfolding processes of SPIs are not a single-step event. Fluorescence phase diagram method was utilized to analyze the unfolding process of SPIs and SPI-casein complexes. The results showed that there was one intermediate (molten globule, MG) in the unfolding process of SPIs, while there were two intermediates (dimer or trimer intermediates and MG) in that of SPI-casein complexes. Further attempts were made to explain the conformational changes of SPIs when binding with casein. The surface hydrophobicity index indicated that the intermediate with strong hydrophobicity was exposed when induced by 2 mol/L urea. The fluorescence quenching experiments using KI as a quencher showed that the Ksv of SPIs and 11S and their complexes with casein all reached peak values when urea concentration was 2 mol/L, while Ksv values of 7S and 7S–casein complex peaked at urea concentration 8mol/L and 6mol/L, respectively. Besides, Ksv and fm changing trends of 7S–casein complex was similar to that of SPIs–casein. Based on the above results, it could be inferred that the interactions between SPIs and casein mainly occurs in 7S. The molecular docking of 7S chains from SPIs and casein showed that SPIs could form a “pocket” conformation to “hold” the casein chain. These findings provide new perspectives for understanding the mechanism of interaction between soy proteins and casein, and may provide a basis for research on the functionality of proteins in the food industry. Note: Ksv is the quenching constant of the quenching agent, and fm is the quenching rate.